Auditoría de gestión y su incidencia en los servicios académicos de la unidad educativa 24 de Mayo, cantón Quevedo, año 2013 - Rodríguez López, Verónica Alexandra (2015)
The realization of this audit in the Education Unit "May 24" includes the study of academic services having as main purpose to get to know their importance in the functional scope and its operational aspects, covering the internal situation the same for take measures to help improve their processes efficiently and effectively. For this reason it was found the following objectives: to evaluate the organizational structure using the Education Unit, determine the level of achievement of objectives, policies and programs and finally check the level of performance of laws and regulations LOEI (Organic Act inductive, descriptive and documentary Intercultural Education), highlighting to get to meet the expectations of this research work methods were used. Types: exploratory and field. Techniques: observation, interview, and questionnaire survey. Research sources: primary and secondary that earned to find results as inadequate division of departments, usencia a vision and mission, incorrect distribution of functions and lack of policies, concluding that the organizational structure used by the Education Unit not accommodate their priorities and needs, and the level of achievement of objectives, policies and programs leading to the expected results may not be achieved and moreover principals and teachers if they govern the LOEI (Organic Law of Intercultural Education) . It is therefore important to establish recommendations invokes the needs of the institution to seek improvement and guide those made within it to improve organizational profile so that they can make sound and timely decisions and thus continue to operate in time with maximum security without any insubordination.